A health utility assessment of trapeziectomy with ligament reconstruction and tendon interposition for thumb trapeziometacarpal osteoarthritis. (September 2019) - Efanov, Johnny Ionut; Nguyen, David-Dan; Izadpanah, Ali; Danino, Michel Alain; Harris, Patrick
Trapeziectomy with ligament reconstruction and tendon interposition (LRTI) for trapeziometacarpal joint osteoarthritis may have both postoperative benefits and complications. This study sought to determine the health state utility outcome measures of trapeziectomy with LRTI. Patients who underwent trapeziectomy with LRTI were invited to complete the brief Michigan Hand Questionnaire and utility questionnaires outcomes using a visual analogue scale, time trade-off and standard gamble. Quality-adjusted life years (QALYs) were derived from these utility measures. For this study 32 patients were recruited, with a mean age of 61. Most patients (27/32) perceived the procedure as successful. Utility measures and QALYs serve the purpose of comparing different surgical procedures in terms of their impact on the quality of life of patients as a function of the benefits and complications of each procedure. In this study, the utility of trapeziectomy with LRTI was less than has been described for open palmar fasciectomy but more than for total wrist arthrodesis. Level of evidence: IV